Lipase immobilization on nylon-6 grafted PGMA polymer to improve enzyme performance and stability - Nik Adlin binti Bahrudin (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Lipase from wheat germ was immobilized by covalent binding on nylon -6- grafted with polyglycidyl methacrylate (PGMA). This polymer was successfully activated with diethyl amine to bond with lipase enzyme molecules. Face centred central composite design (FCCCD) under response surface methodology (RSM) were applied to model and optimize conditions for maximum activity and understanding the interaction of the factors affecting the activity of the immobilized enzyme. The FCCCD was applied to measure the effect of three parameters namely, reaction pH (6-8), immobilization time (2-10h) and enzyme concentration (1-2mg/ml) on enzyme activity. Based on the analysis, the optimum immobilization conditions obtained were at pH 7, immobilization time of 5 hours and enzyme concentration 0.90 mg/ml. The results indicated that the parameters were significant factors on the activity of immobilized lipase. Quadratic polynomial equation was obtained for the immobilized lipase activity. Kinetic parameters KM and Vmax were 7.25 mM and 0.012 respectively. The immobilized lipase was stable at 45°C of pH 8. Operational stability was determined with immobilized lipase and it shows a small deactivation (18%) after being recycled for 8 times. Lastly, in storage stability test, immobilized lipase was able to retain 70% of its activity after being stored for 30 days. Therefore, the nylon-6 grafted PGMA polymer is promising solid support media for enzyme immobilization and this study could be a stepping stone for production of lipases in large scale for wide industrial application. Michelis–Menten kinetic models were applied in this study. Lineweaver -Burk plot were chosen with highest coefficient of determination (R2) 0.988.